When relationships go wrong: insights from previous studies - Lopes, R.; Loureiro, S. M. C. (Proceeding of the 4th International Consumer-brand relationship, 2015)
This research provides a first systematic literature review on negative consumerbrand relationships (NCBR) issues in order to capture the main terms and factors employed in several previous studies.